Oral etoposide and zosuquidar bioavailability in rats: Effect of co-administration and in vitro-in vivo correlation of P-glycoprotein inhibition - Rasmus Blaaholm Nielsen; René Holm; Ils Pijpers; Jan Snoeys; Ulla Gro Nielsen; Carsten Uhd Nielsen (Elsevier, 2021)
P-glycoprotein inhibitors, like zosuquidar, have widely been used to study the role of P-glycoprotein in oral absorption. Still, systematic studies on the inhibitor dose-response relationship on intestinal drug permeation are lacking. In the present study, we investigated the effect of 0.79 nM-2.5 μM zosuquidar on etoposide permeability across Caco-2 cell monolayers. We also investigated etoposide pharmacokinetics after oral or IV administration to Sprague Dawley rats with co-administration of 0.063-63 mg/kg zosuquidar, as well as the pharmacokinetics of zosuquidar itself. Oral zosuquidar bioavailability was 2.6-4.2%, while oral etoposide bioavailability was 5.5 ± 0.9%, which increased with increasing zosuquidar doses to 35 ± 5%. The intestinal zosuquidar concentration required to induce a half-maximal increase in bioavailability was estimated to 180 μM. In contrast, the IC50 of zosuquidar on etoposide permeability in vitro was only 5-10 nM, and a substantial in vitro-in vivo discrepancy of at least four orders of magnitude was thereby identified. Overall, the present study provides valuable insights for future formulation development that applies fixed dose combinations of P-glycoprotein inhibitors to increase the absorption of poorly permeable P-glycoprotein substrate drugs.